2015
DOI: 10.1007/s00122-015-2609-7
|View full text |Cite
|
Sign up to set email alerts
|

Complementary resistance genes in wheat selection ‘Avocet R’ confer resistance to stripe rust

Abstract: Complementary genes for resistance to wheat stripe rust in an Avocet selection mapped to chromosome arms 3DL and 5BL. Susceptible Avocet selections lacked the 5BL gene due to a chromosomal deletion. This study reports the inheritance and genetic mapping of the YrA (temporary name of convenience to describe the specificity) seedling resistance to wheat stripe rust (caused by Puccinia striiformis f. sp. tritici; Pst) in a resistant selection of the Australian cv. Avocet [Avocet R (AvR)-AUS 90660]. Genetic analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 28 publications
1
53
0
Order By: Relevance
“…Qualitative resistance is generally conferred by single genes with large effects against the pathogen and can be observed in both seedling and adult plant stages. To date, 50 loci containing 78 resistant genes/alleles to PM [7,8] and 74 genes ( Yr1 – Yr74 ) to YR [9,10] have been identified in bread wheat and its relatives. This type of resistance has a strong tendency to be overcome by new races, particularly when a single gene is deployed over large areas.…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative resistance is generally conferred by single genes with large effects against the pathogen and can be observed in both seedling and adult plant stages. To date, 50 loci containing 78 resistant genes/alleles to PM [7,8] and 74 genes ( Yr1 – Yr74 ) to YR [9,10] have been identified in bread wheat and its relatives. This type of resistance has a strong tendency to be overcome by new races, particularly when a single gene is deployed over large areas.…”
Section: Introductionmentioning
confidence: 99%
“…A large translocation on chromosome 6AL from Thinopyrum ponticum (carrying the wheat stem rust resistance gene Sr26 ) contributed by the AvR parent explains the large linkage block on chromosome 6A in the T/A genetic map. The second translocation is the widely reported 5B:7B reciprocal translocation derived from the Teal parent, which was also identified in the genetic map of the T/A DH population (Dracatos et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Selected linkage groups of the genetic map for the Teal × Avocet R wheat doubled haploid population (Dracatos et al ., ) showing the stable quantitative trait loci ( QTL ) identified in both phenotypic replicates (green and blue corresponding to replicates 1 and 2, respectively). The name on QTL bars has two components: the provisional name of the gene at the QTL and the logarithm of odds ( LOD ) value recorded for the QTL .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2000, 21 new races of stripe rust were identified in the United States, and among these new races, eight had combinations of virulence to resistance genes that were previously known to provide exceptional resistance in the United States (Chen et al, 2002). This new stripe rust population has increased adaptation and fitness yet contains many virulence alleles that are not required to overcome resistance in soft red winter wheat cultivars east of the Rocky Mountains (Chen, 2005;Dracatos et al, 2016). New races were identified that are able to germinate at warmer temperatures, allowing for disease development later in the season.…”
mentioning
confidence: 99%